Zastosowanie drążenia danych w zarządzaniu relacjami z klientami (CRM) - Bandosz, Marcin (Data mining application in Customer Relationship Management (CRM), 2005)
The article presents the selected ways of using methods of data mining in behavior and needs of customers. The most important advantages and the most common problems of different techniques of data mining have been described. The examples of usage of analytical CRM have been presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1064, s. 23-29